Le sensorium synthétique : réflexion sur l’utilisation de l’expographie immersive numérique et muséale - Dominique Gélinas (Conserveries Mémorielles)
Over the past decade, digital technologies have been increasingly used to showcase heritage, notably in museums. Many professionals want to improve the experience of visitors. They want to make a significant impact to ensure repeat visits. The use of 3D models, augmented reality, and wide screens to enhance exhibits often comes with enthusiastic claims that promise the moon and the stars. Immersive exhibits have also made a comeback due to their emotional impact on visitors. Rarely accompanied by written explanations, their content is usually processed intuitively rather than through descriptive means.This article aims to explore the possibilities of replacing material immersion in exhibitions with digital immersion, and how to tackle the particularities of this new virtual immersive experience. As a starting point, this paper brings to light the many definitions of immersion and how they have changed over time.First, I begin with an overview of the different ways immersive exhibits have been analyzed since their revival in the 1970s and 1980s. I am not interested in writing the history of the different devices used, but rather to get a sense of how professionals perceived and used this type of exhibit. For a long time, the museum exhibition has been understood as an intellectual process that is analogous to an illustrated text. However, immersion has been used for over a century (panoramas, period rooms, dioramas, domes, etc.) not only to encourage comprehension, but also to provoke an emotional response towards the heritage content being showcased. The immersive experience articulates itself through its own mechanism that cannot be replicated by using a traditional approach of objects in display cases. Starting with this mechanism, which involves corporal and sensorial approaches, the paper moves on to its second theme, which is the theoretical framework of sensible anthropology. This theory has resurfaced in the early years of the millennium following the rediscovery of the importance of senses through the emergence of new ethno-anthropological paradigms. I seek to apply this theory to immersive exhibits by highlighting the complexity of such an approach. Finally, I have focused on the shift from material to digital immersion. This entails outlining the concept of remediation, which leads to reflections on the use of technology. I have tried to identify the main ideas emerging from the museum sector relating to remediated immersive digital exhibits. I end with a critical stance that questions digital immersion in itself. I conclude that museum practitioners have an imperfect understanding of these new tools, being unable to truly understand their limitations. The amalgamation of digital technologies with the underlying principles of museum exhibits is not always as simple as it may seem. If professionals want to go further than what they already know, this will need to be tested. Moreover, many professionals, such as archeologists, architects involved in heritage conservation, and historians use 3D models and other technologies. Museum practitioners will soon have to follow suit without fearing the loss of material content in the face of digital technologies.